PENGARUH KOMUNIKASI ORANG TUA TERHADAP PERILAKU ANAK - Pismaria Cema Maria (Prodi PIAUD, Fakultas Tarbiyah dan Keguruan, UIN Sulthan Thaha Saifuddin Jambi, 2022)
This article aims to determine the effect of parental communication on children's behavior. Several research results from various journals state the influence of parental communication on children's behavior. There are several reasons why this can happen, one of which is because if parents do not interact intensely with their children, it is possible that children have less than optimal cognitive development, so that this affects their behavior, this influence can last even until the child is an adult. Even though the world is developing rapidly in the field of telecommunications, both through social media and other media, this does not allow communication between parents and children if there is no verbal interaction and dealing with children.